2010
DOI: 10.1161/hypertensionaha.108.127456
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiotensin II in the Remodeling Induced by a Chronic Increase in Flow in Rat Mesenteric Resistance Arteries

Abstract: Abstract-Angiotensin II is a potent growth factor involved in arterial wall homeostasis. In resistance arteries, chronic increases in blood flow induce a rise in diameter associated with arterial wall hypertrophy. Nevertheless, the role of angiotensin II in this remodeling is unknown. We investigated the effect of blocking angiotensin II production or receptor activation on flow-induced remodeling of mesenteric resistance arteries. Arteries were ligated in vivo to generate high-flow arteries compared with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 42 publications
3
33
1
Order By: Relevance
“…Interestingly, in a previous work, we showed that in response to a chronic increase in flow, angiotensin II induces hypertrophy (through AT1R) without eliciting any change in diameter, 16 whereas this study shows that in response to a decreased flow, angiotensin II controls the diameter change without obvious effects on wall mass. Thus, in ischemia (with reduced flow in ischemic tissues and a rise in flow in the surrounding tissues), blocking the AT1R might have a doubly beneficial effect, preventing any reduction in diameter in the ischemic zone and reducing hypertrophy in the feeding arteries that are sometimes recruited to vascularize the ischemic tissue.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Interestingly, in a previous work, we showed that in response to a chronic increase in flow, angiotensin II induces hypertrophy (through AT1R) without eliciting any change in diameter, 16 whereas this study shows that in response to a decreased flow, angiotensin II controls the diameter change without obvious effects on wall mass. Thus, in ischemia (with reduced flow in ischemic tissues and a rise in flow in the surrounding tissues), blocking the AT1R might have a doubly beneficial effect, preventing any reduction in diameter in the ischemic zone and reducing hypertrophy in the feeding arteries that are sometimes recruited to vascularize the ischemic tissue.…”
Section: Discussioncontrasting
confidence: 72%
“…As we have previously shown 16 that angiotensin II-induced contraction was mediated by the activation of ERK1/2 in mesenteric RAs, we tested the effect of ERK1/2 blockade on vascular contractility in LF arteries. Indeed, the inhibition of ERK1/2 by PD98059 decreased angiotensin II-induced contraction in NF arteries and suppressed the phenomenon in LF vessels (Figure 6a).…”
Section: Reactive Oxygen Species (Dhe Staining)mentioning
confidence: 99%
See 2 more Smart Citations
“…The final step, leading to diameter enlargement, requires a dilator stimulus (17). Flow-mediated outward remodeling is also associated with a compensatory increase in wall mass (11,32) due to ANG II type 1 receptor activation of ERK1/2 (11).…”
mentioning
confidence: 99%